ALEGLITAZAR – AN UPCOMING DUAL PPAR ALPHA/GAMMA AGONIST REDUCING THE MACRO VASCULAR RISKS ASSOCIATED WITH TYPE 2 DIABETES MELLITUS - C.ANIRUDH JAGANNADH; M.SRAVANI; DR M.D DHANARAJU (International Journal of Pharma and Bio Sciences, 2013)
Diabetes is a chronic disorder frequently associated with failure of vital organs like eyes, heart,kidneys, nerves, and blood vessels. Treatment of diabetic complications with drugs was classified as monotherapy, dual therapy and triple therapy. Many patients cannot obtain satisfactory glycemic control with current therapies, and eventually develope micro vascular and macro vascular complications. New and more effective agents targeted for therapy are required.This review focuses on the therapeutic potential of novel dual PPAR alpha/gamma agonist ,aleglitazar in comparision with PPARγ agonists.Aleglitazar exerts dual effects in lowering plasma triglycerides and increasing HDL cholesterol and is the first target for reducing cardiovascular risk among Glitazars. Further studies are needed to provide benefits of cardiovascular events and changes in long term lipid profiles.